Re: playing trauma: the potential of using re-enactment as a possible way of processing childhood trauma in drama therapy - Bradshaw, Mirella Elizabeth (My University, 2022)
Evidence suggests that the presence of childhood trauma may be linked to the development of a variety of mental illnesses later in life; borderline personality disorder is one of these such illnesses with a broad scope of literature supporting this link. Further, due to the high rates of trauma present in South African society compounded by the COVID-19 pandemic, it is the author’s view that innovative approaches to working with trauma are currently of vital importance. Psychology research speaks to the potential of exposure therapy in trauma treatment, while literature from both drama therapy and psychology emphasizes the importance of an embodied approach in trauma work. Therefore, through an examination of relevant literature, this research sought to understand the potential use of re-enacting trauma within drama therapy as part of the therapeutic process. Using the method of an integrative literature review, relevant literature was analysed using thematic analysis. This research found that reenactment could be considered as a useful tool in processing trauma, provided that the exposure is done in a gradual way and care is taken to try to not re-traumatise the client. Further, the literature pointed to the value of using role to support re-enactment, and the importance of providing the client with an opportunity to rescript their trauma towards regaining a sense of agency and control. Recommendations for further research are suggested.
A research report submitted to the School of Arts, Faculty of Humanities, University of the Witwatersrand in partial fulfilment of the requirements for the degree of Master of Arts by coursework and research report in the field of Drama Therapy, 2022